A Simple Method for the Determination of Polyphenolic Compounds from Grapevine Leaves - Petra Štambuk; Marina Anić; Nera Huzanić; Darko Preiner; Marko Karoglan; Jasminka Karoglan Kontić; Ivana Tomaz (Separations, 2022)
Grapevine leaves are photosynthetically the most active green organs providing carbohydrates that are of utmost importance for the regular vine’s metabolism and growth. Moreover, leaves are the pioneers of fungal infections caused by B. cinerea, E. necator, and P. viticola. Plant response to these microorganisms mostly depends on the content and composition of phenolic compounds abundantly found in the leaf’s outer tissues (epidermis, cuticle, trichomes). In order to obtain a satisfactory quantity of phenolic compounds, an experiment was conducted towards optimizing a solid–liquid extraction method. Variables were as follows: the type of organic solvent, the sample weight, the extraction temperature, and the extraction time. The optimal conditions were obtained by applying the response surface methodology. Therefore, by using acetonitrile as the organic solvent, conducting a single-step extraction at the temperature of 48 °C during the time period of 2 h and 25 min with a solid-to-solvent ratio of 1:56 g mL−1 (178 mg of leaves powder and 10 mL of extraction solvent) the optimal content of phenolic compounds was obtained. This protocol is reliable, fast, and relatively easy to perform for the determination of the abovementioned compounds.